1995
DOI: 10.1016/s0022-5223(95)70070-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of retrograde cerebral perfusion after particulate embolization to the brain

Abstract: Neurologic injury as a consequence of cerebral embolism of either air or atherosclerotic debris during cardiac or aortic surgery is still a major cause of postoperative morbidity and mortality. While exploring various means of improving cerebral protection during complex cardiothoracic procedures, we have developed a chronic porcine model to study retrograde cerebral perfusion. We have previously demonstrated that retrograde perfusion results in a small amount of nutritive flow and provides cerebral protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Sa® et al [19] also reported that RCP was better than HCA, but did not study HCA with ice-packing of the head. Yerlioglu et al [25] reported that RCP and anterograde perfusion resulted in complete behavioral recovery, but that embolization resulted in poorer recovery, especially with RCP of .40 mmHg.…”
Section: Neurological Outcome In Laboratory Investigationsmentioning
confidence: 99%
“…Sa® et al [19] also reported that RCP was better than HCA, but did not study HCA with ice-packing of the head. Yerlioglu et al [25] reported that RCP and anterograde perfusion resulted in complete behavioral recovery, but that embolization resulted in poorer recovery, especially with RCP of .40 mmHg.…”
Section: Neurological Outcome In Laboratory Investigationsmentioning
confidence: 99%
“…When proximal anastomosis of the descending thoracic aorta is performed through left thoracotomy, the most dependent portion of the aorta is the aortic root or cerebral vessels [12]. Therefore, the chances of embolic cerebral infarction from debris may increase.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on RCP yields conflicting results; however, most authors believe that RCP does not prolong the safe duration of DHCA. On the other hand, RCP may be effective at minimizing particulate embolization to the brain (12). Thus, RCP is reserved for patients with a high atherosclerotic burden in the aortic arch.…”
Section: Arch Replacement With Axillary Cannulationmentioning
confidence: 99%